Kecakapan Hidup pada Atlet UKM Pickleball Universitas Jambi - Natavia, Firdha Wulan; Hadinata, Reza; Khairunnisa, Fitri (MAN Insan Cendekia Jambi, 2025)
This research aims to identify the level of life skills among members of the Pickleball Sports Club at Jambi University across eight aspects: teamwork, goal setting, time management, emotional competence, interpersonal communication, social skills, leadership, and problem-solving and decision-making. This quantitative descriptive study was conducted at the JPOK Field of Jambi University during regular training sessions in January 2025, with a population of 50 people and a sample of 20 active members. Data collection was carried out through questionnaires using a Likert scale and the Life Skill Scale for Sport (LSSS) instrument. The results show that most athletes demonstrate good proficiency in these aspects, with social skills being the most dominant component rated in the high and very high categories. Leadership aspects also showed positive results through a leadership rotation system that enhances leadership abilities. However, time management and goal-setting aspects still require further development. This study concludes that Pickleball sports positively contribute to the development of life skills among club members, with social skills being the most prominent component supporting team success.